Self-Adaptive RISs Beyond Free Space: Convergence of Localization, Sensing, and Communication Under Rich-Scattering Conditions - Saigre-Tardif, Chloe; del Hougne, Philipp (IEEE wireless communications, 2023)
We discuss the need for a confluence of localization, sensing, and communications if reconfigurable intelligent surfaces (RISs) are to be deployed in a self-adaptive manner in the dynamically evolving rich-scattering settings that are typical for important 6G deployment scenarios, such as factories. We establish that in such problems the rich-scattering wireless channels are subject to a highly nonlinear deterministic double-parametrization through both the RIS and uncontrolled moving objects. Therefore, acquiring full context-awareness through localization and sensing is a prerequisite for self-adaptive RIS-empowered communications. Yet, the byproducts of this daunting communications overhead can feed many appliances that require context awareness, such that overhead concerns may vanish. We illustrate the essential steps for operating a self-adaptive RIS under rich scattering based on a prototypical case study. We discover that self-adaptive RISs outperform context-ignorant RISs only below a certain noise threshold that depends, among other factors, on how strongly uncontrolled perturbers impact the wireless channel. We also discuss ensuing future research directions that will determine the conditions under which self-adaptive RISs may serve as technological enabler of 6G networks.